2010
DOI: 10.1097/fjc.0b013e3181ce5f5a
|View full text |Cite
|
Sign up to set email alerts
|

Pravastatin Counteracts Angiotensin II-Induced Upregulation and Activation of NADPH Oxidase at Plasma Membrane of Human Endothelial Cells

Abstract: Endothelial dysfunction has been linked to reactive oxygen species (ROS) production by nicotinamide adenine dinucleotide phosphate reduced (NADPH) oxidase. Angiotensin II (ANG), which levels are elevated in some cardiovascular diseases, can stimulate this enzyme, whereas statins have been demonstrated pleiotropic effects related with the restoration of endothelial function. Therefore, our purpose was to study the mechanism of the possible beneficial effects of pravastatin on ANG-activated human umbilical vein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 32 publications
0
44
0
Order By: Relevance
“…Simvastatin was activated by opening the lactone ring by dissolving in 95% ethanol and 0.1 N NaOH, heating at 50°C for 2 hours, and neutralizing with HCl to pH 7.2, as described previously (Gerson et al, 1989;Tawfik et al, 2006). The doses of statins were chosen on the basis of previous studies (Dje N'Guessan et al, 2009;Alvarez et al, 2010) and our observations that statins at these doses did not significantly induced morphologic signs of cytotoxicity in HCAECs. Some groups of cells were pretreated with mevalonate (10 mM), farnesol (10 mM), geranylgeraniol (10 mM), methyl-b-cyclodextrin (1 mM), or filipin (1 mg/ml; all reagents were purchased from Sigma-Aldrich) for 1 hour.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Simvastatin was activated by opening the lactone ring by dissolving in 95% ethanol and 0.1 N NaOH, heating at 50°C for 2 hours, and neutralizing with HCl to pH 7.2, as described previously (Gerson et al, 1989;Tawfik et al, 2006). The doses of statins were chosen on the basis of previous studies (Dje N'Guessan et al, 2009;Alvarez et al, 2010) and our observations that statins at these doses did not significantly induced morphologic signs of cytotoxicity in HCAECs. Some groups of cells were pretreated with mevalonate (10 mM), farnesol (10 mM), geranylgeraniol (10 mM), methyl-b-cyclodextrin (1 mM), or filipin (1 mg/ml; all reagents were purchased from Sigma-Aldrich) for 1 hour.…”
Section: Methodsmentioning
confidence: 99%
“…By interfering with cholesterol biosynthesis and lowering plasma membrane cholesterol levels, statins were shown to decrease the expression of caveolin-1, resulting in eNOS activation and nitric oxide production (Mason et al, 2004). Second, by preventing isoprenylation of Rac1, which is important for NADPH oxidase activation, recent studies have revealed that statins inhibit O 2 .2 formation in ECs after stimulation of injury factors or under pathologic conditions, such as angiotensin II, homocysteine, and hyperglycemia (Wagner et al, 2000;Vecchione et al, 2007;Briones et al, 2009;Alvarez et al, 2010;Bao et al, 2010c). However, it remains unknown how statins alter the assembling and aggregation of NADPH oxidase subunits and, thereby, affect its activity to produce O 2 .2 in addition to their effect on Rac1 or eNOS.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, pravastatin and fluvastatin had a direct scavenging radical activity Kassan et al, 2010). Pravastatin was also reported to inhibit the stimulatory activity of angiotensin II on NADPH oxidase, thereby contrasting the production of superoxide radicals (Alvarez et al, 2010).…”
Section: B Statins and Endothelial Functionmentioning
confidence: 99%
“…A number of retrospective and prospective studies have demonstrated the potential protective effect of statins on CIN (9)(10)(11). In addition, statins have been reported to exhibit antioxidant effects through decreasing the mRNA expression of NOX4 and p22phox (12,13). These findings suggest that statins may exhibit a protective effect in CIN through decreasing the expression of NOX4 and p22phox in kidney cells.…”
Section: Introductionmentioning
confidence: 54%